Reflexos da recuperação da baleia jubarte: tendências de produção científica e dinâmica espaço-temporal de grupos competitivos no Banco dos Abrolhos, atlântico sul ocidental - Bonfim, Waltyane Alves Gomes (2017)
The humpback whale is a cosmopolitan species that, due to hunting, had a reduction of about 90% in all its populations. Since 1986, with the prohibition on whaling and the implementation of conservation measures, this species has begun a process of recovery. It is now necessary to understand how these recovered populations will interact with the new environmental scenarios. In this context, scientometrics is an innovative tool that can help researchers to identify trends in knowledge of species or research areas. Thus, we constructed a large bibliometric dataset to analyse research on Megaptera novaeangliae. For that, we used 581 articles from web of science database. We found a total of 984 authors involved in the surveys, which were published in 125 journals. USA, Australia, Canada and Brazil are the most productive countries. Despite this, more than 50% of all researches are only about US Coastal Populations. We discuss factors that may encourage scientific interest in humpback whale, such as investment in researches, populations’ proximity and whaling culture and possible new directions for research. The population of Humpback Whales in the South Western Atlantic is one of the 7 recognized migratory stocks in the Southern Hemisphere. Due to hunting, this population has been reduced to about 2% of its original size but is currently in a successful process with growth rates of 25% in 4 years. With the growth, the species has reoccupied its original occurrence area off the coast of Brazil, remaining concentrated in the Abrolhos Bank - BA. This study was based on 855 competitive groups, a type of grouping in which males compete for female access, monitored between 1992 and 2016, from July to November, on 3 to 5 day research cruises. We tried to understand the temporal and spatial patterns of the 855 groups. The number of groups sighted each season varied between 3 and 53, growing each season. Of the 855 groups sighted, 23% had calves and the size of the group ranged from 3 to 14 adult whales. Most of the groups remained in an area with an average depth of 78m, usually under similar latitudes and longitudes. We found a relationship between the number of competitive groups and the number of stranded calves and a better investigation of the influence of these groups on parental care is needed. The finding of areas of concentration of competitive groups, especially with calves, in areas outside the Abrolhos National Marine Park, can subsidize discussions about the need to protect new areas.